Electro-Convulsive Therapy (ECT): In the Eyes of Nurses of a Tertiary-Care Hospital (Health Renaissance, 2011)
Background:Electro-convulsive therapy (ECT) is frequently viewed negatively, even among health professionals. Such a view might have adverse consequences. Objective: To explore how nursing students and nursing staff view ECT. Methodology: This is a semi-qualitative attitudinal study and the views were compared between nursing .student. and .staff. groups. A questionnaire prepared to assess views about different aspects of ECT was distributed among nursing students and staff of a tertiary-care hospital with a psychiatric service, after an explanation. The questionnaire focused mainly on effectiveness, safety, use, acceptance and some local issues. Results: A total of 108 subjects included 54 nursing staff and students each. Average student age was 21 and staff 29 years. Nearly one-third of students were interested in psychiatry for career versus only 13% staff. The majority of students had seen ECT being given, compared with 40% of staff. Depression was stated as an indication by 62% students versus 40% of staff. More staff thought ECT was more expensive than drugs. More staff indicated adverse effects as a main obstacle while using ECT than students. More students thought it .very effective. versus staff. Regarding safety, both had comparable views, but more staff viewed it as dangerous. More students than staff felt it should be promoted and public awareness should be raised. More students expressed readiness to use ECT if needed for themselves or relatives. Conclusion: Nursing students had more favorable views towards ECT than nursing staff. Keywords: Electroconvulsive therapy; knowledge attitude; nurse; psychiatric morbidity DOI: 10.3126/hren.v8i2.4417 Health Renaissance, May-Aug 2010; Vol 8 (No.2):85-89